Assessing the implications of sentinel lymph node removal in cervical cancer: an immunogenetic perspective – a SENTICOL ancillary study - Alejandra Martinez; Gwenael Ferron; Fabrice Lécuru; Patrice Mathevet; Maha Ayyoub; Anne-Sophie Navarro; Arash Rafii; Anna Salvioni; Marie Michelas; Gaurav Thareja; Françoise Lauzeral-Vizcaino; Najeeb Halabi; et al. (Journal for ImmunoTherapy of Cancer)
Background Cervical cancer’s lymphatic spread primarily begins from the sentinel lymph nodes (SLNs), underlining their pivotal role in disease metastasis. However, these nodes’ immune gene expression profiles and immunoregulation mechanisms have yet to be explored.Methods Our study aimed to elucidate the immune cell populations and their roles in the immune gene expression profile of negative SLNs compared with positive SLNs and non-SLNs using Nanostring RNA seq analysis. We performed a principal component analysis on the log2 normalized expression of 685 endogenous genes in the nCounter PanCancer Immune Profiling Panel, followed by an assessment of the differential expression of genes and immune cell type abundance.Results We found significant variations in gene expression among the groups, with negative SLNs displaying overexpression of genes related to tumor-infiltrating immune cells, specifically innate cell populations. They also demonstrated the upregulation of genes involved in antigen presentation and T-cell priming. In contrast, positive SLNs were enriched in regulatory networks, suggesting their potential role in immune evasion. A comparison of negative SLNs and non-SLNs revealed increased innate and adaptive immune cell types, underscoring the ongoing T cell response to tumor antigens.Conclusion Our findings underscore a specific immunogenetic phenotype profile in negative SLNs, emphasizing their crucial role in the initial anticancer response, immunosurveillance, and the propagation of immune tolerance from the primary cervical tumor. These results highlight the potential of SLNs as a novel target for immunotherapy strategies and underscore the importance of new imaging methods for accurately identifying SLN status without removal. Future investigations are needed to understand further the immunological interplay within SLNs and their influence on cervical cancer progression.